The Profile of Pekalongan as a Center of Economic Growth at Tangkallangka Strategic Areas - Karsinah, Karsinah; Putri, Phany Ineke; Rahayu, K. Nurjannah; Panjiputri, Agata Febrina (International Journal of Economics and Financial Issues, 2016)
This study aims to analyze leading sectors, economic interactions and development strategies of Pekalongan as center of economic growth at Tangkallangka Strategic Areas. Data used in this research are primary and secondary ones. Methods used for data collection are interviews, questionnaries and documentation. Data are then analyzed using Location Quotient (LQ), Growth Ratio Model (GRM), Overlay, Gravity, and SWOT Analysis. The results show that Pekalongan has some leading sectors which have competitive and comparable potentials in infrastructures, trades and finances. Pekalongan has the greatest spatial interaction with Batang. Aggressive strategies are used in developing Pekalongan. Keywords: Regional Development, Growth Center, Klassen Typological Analysis, JEL Classifications: B22; D60 ; O18